2018
DOI: 10.1016/j.jsg.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Tracking mechanical Dauphiné twin evolution with applied stress in axial compression experiments on a low-grade metamorphic quartzite

Abstract: The stress-dependent evolution of mechanical Dauphiné twinning has been investigated in axial compression experiments on a low-grade metamorphic quartzite, applying both time-of-flight neutron diffraction and electron backscatter diffraction. The data of the experimentally stressed quartzite samples were compared with those of the naturally deformed starting material to monitor Dauphiné twinning in relation to different experimental stress states. This comparison shows that in the experimental conditions of 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
(57 reference statements)
1
11
0
Order By: Relevance
“…All of these samples are Triassic quartzites. Similar high ratios were observed for experimentally stressed quartzites [143] that we show for comparison as sample Br in Table 2C.…”
Section: Mechanical Dauphiné Twinningsupporting
confidence: 90%
See 2 more Smart Citations
“…All of these samples are Triassic quartzites. Similar high ratios were observed for experimentally stressed quartzites [143] that we show for comparison as sample Br in Table 2C.…”
Section: Mechanical Dauphiné Twinningsupporting
confidence: 90%
“…After discussing the geological significance of these observations of quartz preferred orientation, let us look at some methodological aspects. As was mentioned earlier, a range of methods were used to investigate quartz textures, ranging from optical methods [148,149], conventional X-ray diffraction [19,65], synchrotron X-ray diffraction [150,151], neutron diffraction (ranging from monochromatic [149,152] to time-of-flight [49]), and electron backscatter diffraction (EBSD) [79,143,144,146]. Results from different methods were compared [25,49,63,149,153,154].…”
Section: Comparison Of Methods Of Texture Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the z orientation lacks orientations parallel to the vorticity axis (center of pole figure) as well as along the upper left and lower right margins of the pole figure. Both experimental [85] and observational [86][87][88] studies have shown that rhomb-dominated fabrics may develop even in the absence of strong c-axis fabrics. This pattern reflects Dauphiné twinning (a 60°rotation around the quartz crystallographic c-axis) triggered by a response to stress.…”
Section: Crystallographic Analysismentioning
confidence: 99%
“…These twins are common in quartz, both as growth twins and as deformation twins (e.g. Minor et al 2018).…”
Section: T E S T W I T H B O U D I N a G E S A M P L E B E -Dmentioning
confidence: 99%